Forging a Stronger Link: Unveiling The Synergy Between Supply Chain Integration and Risk Management in Tin Mining Industry - Dony Saputra; Christy Olivianny (School of Business, Bogor Agricultural University (SB-IPB), 2025)
Background: Operational performance faces many challenges in the production of tin especially for Indonesia as the global market leader. Optimization of its operational performance by bolstering its supply chain integration such as customer integration in downstream processes and integration internally is a big challenge with the lack of smelter though it has been catalyzed by Indonesian government regulation. Additionally, supply chain risk management has been considered important globally to the sustainability and environmental awareness of a tin company related to its operational performance and supply chain integration.Purpose: This research aims to investigate how internal integration and customer integration, mediated by supply chain risk management, affect operational performance in a tin mining company. Design/methodology/approach: Employing a quantitative associative design and proportionate stratified random sampling method used in this study. Data from 47 employees from seven divisions of a tin company in Indonesia were collected and analyzed using PLS-SEM analysis on SMART PLS 3.29 software. Findings/Result: Results indicate a significant positive relationship between customer integration and operational performance, mediated by supply chain risk management. Contrary to expectations, internal integration did not significantly influence operational performance, either directly or indirectly.Originality/value (State of the art): These findings contribute to the evolving body of knowledge on supply chain integration by highlighting the critical role of customer-centric approaches in enhancing operational effectiveness within the tin mining sector. For practical implication, Effective collaboration, knowledge sharing, and understanding customer needs are key factors in achieving success in supply chain management. Keywords: customer integration, internal integration, supply chain, risk management, operational performance